Phenotypic variability for conformation traits of BON cattle in Colombia - Medina Ríos, Hernán Issaías; Ramírez Toro, Edison Julián; Cerón Muñoz, Mario Fernando; Burgos Paz, William (Researcher, 2024)
The purpose of this study was to evaluate the variability of conformation traits (CT) in three BON cattle subpopulations with different herd management. For this study, using the nine-point scores of 20 CT as well as breed characterization and nal score in 929 cows were analyzed. Descriptive statistics alongside hierarchical cluster analysis were performed. It was found that legs and feet traits had the slightest phenotypic variability whereas traits related to musculature and the fore attach and udder depth traits showed the higher variability. The herarchical clustering revealed relationships that allow analyzing the phenotypic trend between animals according to herd management and breeding objectives.